111. Impairment of synaptic plasticity in patients affected by brain tumors. Issue 1 (January 2015) - Allegra, C.; Maggio, R.; Marino, M.; Terranova, C.; Rizzo, V.; Girlanda, P.; Quartarone, A.
<x xml:space="preserve">Abstract</x> Aim of the present study was to investigate motor cortex synaptic plasticity in both hemispheres of patients affected by brain tumors. We employed an electrophysiological protocol, named repetitive paired associative stimulation (rPAS), involving repetitive transcranial magnetic stimulation (rTMS) paired with electrical stimulation of the contralateral median nerve, that modifies cortico-spinal excitability. Ten right-handed patients (3 women), aged 49–70 years (mean age: 54.8 years), participated in the study. Motor evoked potentials (MEP) were measured at baseline before and for up to 30 min after 5 Hz-rPAS in abductor pollicis brevis (APB). rPAS consisted of 600 pairs of transcranial magnetic stimuli, at a rate of 5 Hz for 2 min, coupled with electrical median nerve stimulation preceding TMS over the contralateral M1 at an interstimulus interval of 25 ms. In both hemispheres of patient with brain tumors rPAS did not induce any significant changes in MEP amplitudes, compared with aged matched healthy controls. Synaptic plasticity is impaired in both hemispheres of patients affected by brain tumors.